Reaction pathway in the WO3-CuO-Mg-C system at nonisothermal conditions - S. Aydinyan; H. Kirakosyan; O. Niazyan; M. Tumanyan; Kh. Nazaretyan; S. Kharatyan
The mechanism of tungsten (VI) and copper (II) oxides co-reduction by Mg+C mixture was investigated at non-isothermal conditions in a wide range of heating rates: i. carrying out combustion process in the copper wedge, ii. using high-speed temperature scanner (HSTS-1), iii. performing differential thermal (DTA) and thermal-gravimetric (TG) analyses combined with X-ray diffraction (XRD) analysis of intermediate and final products. The sequence of chemical reactions occurring during the heating process on the basis of copper wedge results, HSTS analysis, DTA/TG curves and XRD analyses results of quenched reaction products have been proposed. It was revealed that the carbothermic reduction preceded the magnesiothermic reduction process. Due to the suggested reaction pathway, the combined and complete reduction of oxides by Mg/C reducing mixture becomes possible at relatively low temperatures.
Keywords: Physics; Cross-Disciplinary